The safety and efficacy of benzbromarone in gout in Aotearoa New Zealand. Issue 9 (16th September 2016) - Stamp, L. K.; Haslett, J.; Frampton, C.; White, D.; Gardner, D.; Stebbings, S.; Taylor, G.; Grainger, R.; Kumar, R.; Kumar, S.; Kain, T.; Porter, D.; et al.
Abstract : Background: Benzbromarone is a potent uricosuric but is not widely available due to concerns about hepatotoxicity. In Aotearoa New Zealand, benzbromarone has been available since April 2013, subject to funding restrictions, for patients with inadequate urate‐lowering response or intolerance to allopurinol and probenecid. Aim: To assess the safety and efficacy of benzbromarone in a real‐life setting. Methods: All patients who received funding for benzbromarone from 1 April 2013 to 30 September 2014 were identified. Prescribers were sent a questionnaire for each individual. Information on demographics, efficacy of previous urate‐lowering drugs and reasons for discontinuation were collected. Specific information about the dose, effect on serum urate, adverse effects and liver function tests after commencing benzbromarone was recorded. Results: Completed questionnaires were returned for 123 of 164 (75%) patients. Mean (SD) serum urate prior to benzbromarone was 0.57 (0.12) mmol/L, and estimated glomerular filtration rate was 50.3 (22.8) mL/min/1.73 m 2 . The median dose of benzbromarone was 100 mg/day (25–200 mg/day). Six months after commencing benzbromarone, mean (SD) serum urate was 0.35 (0.12) mmol/L. Benzbromarone‐related adverse events included rash ( n = 4), diarrhoea ( n = 9), nausea ( n = 6) and urate stones ( n = 3). Liver function test abnormalities were uncommon and tended to be mild. There were 14 patient deaths; none was considered related to benzbromarone. Allopurinol had been prescribed prior to benzbromarone in 117 of 123 patients; median maximum allopurinol dose was 200 mg/day (range 25–600 mg/day), and 19% patients received allopurinol >300 mg/day. Conclusion: Benzbromarone provides useful urate‐lowering efficacy and does not appear unsafe in patients with gout. Urate‐lowering therapy prescribing requires further optimisation.